The Development of Three Long Universal Nuclear Protein-Coding Locus Markers and Their Application to Osteichthyan Phylogenetics with Nested PCR - Shen, Xing-Xing; Liang, Dan; Zhang, Peng (PLOS ONE, 2012)
Background Universal nuclear protein-coding locus (NPCL) markers that are applicable across diverse taxa and show good phylogenetic discrimination have broad applications in molecular phylogenetic studies. For example, RAG1, a representative NPCL marker, has been successfully used to make phylogenetic inferences within all major osteichthyan groups. However, such markers with broad working range and high phylogenetic performance are still scarce. It is necessary to develop more universal NPCL markers comparable to RAG1 for osteichthyan phylogenetics. Methodology/Principal Findings We developed three long universal NPCL markers (>1.6 kb each) based on single-copy nuclear genes (KIAA1239, SACS and TTN) that possess large exons and exhibit the appropriate evolutionary rates. We then compared their phylogenetic utilities with that of the reference marker RAG1 in 47 jawed vertebrate species. In comparison with RAG1, each of the three long universal markers yielded similar topologies and branch supports, all in congruence with the currently accepted osteichthyan phylogeny. To compare their phylogenetic performance visually, we also estimated the phylogenetic informativeness (PI) profile for each of the four long universal NPCL markers. The PI curves indicated that SACS performed best over the whole timescale, while RAG1, KIAA1239 and TTN exhibited similar phylogenetic performances. In addition, we compared the success of nested PCR and standard PCR when amplifying NPCL marker fragments. The amplification success rate and efficiency of the nested PCR were overwhelmingly higher than those of standard PCR. Conclusions/Significance Our work clearly demonstrates the superiority of nested PCR over the conventional PCR in phylogenetic studies and develops three long universal NPCL markers (KIAA1239, SACS and TTN) with the nested PCR strategy. The three markers exhibit high phylogenetic utilities in osteichthyan phylogenetics and can be widely used as pilot genes for phylogenetic questions of osteichthyans at different taxonomic levels.